Mites (Acari) of cassava (Manihot esculenta Crantz) habitat in southern Africa - Zannou, I.; Hanna, R.; Moraes, G.J. de; Kreiter, S.; Phiri, G.; Jone, A. (Informa UK Limited, 2005)
Consideration of possible side-effects of exotic biological control agents on their new environments is a necessary step in classical biological control programs. The evaluation of such effects usually requires the knowledge of the fauna present in those environments prior to introduction of control agents. This paper presents the first of a series of studies to evaluate the safety of a classical biological control program of the cassava green mite Mononychellus tanajoa (Bondar) in Mozambique and Malawi involving the introduction of Typhlodromalus aripo DeLeon, a predatory mite of the family Phytoseiidae. The objective of this study was to determine the mite fauna of cassava and of some of the visually most common plant species in or around cassava fields in those countries. The study was conducted at different occasions in the dry and rainy seasons, in 26 fields in Mozambique and 20 fields in Malawi representing a range of ecosystems. Twenty-one phytoseiid species were recorded in Mozambique and 32 in Malawi. On cassava, the dominant phytoseiids were Euseius baetae (Meyer & Rodrigues), Euseius bwende (Pritchard & Baker) and Typhlodromalus saltus(Denmark & Muma) in Mozambique, and Euseius fustis (Pritchard & Baker), Iphiseius degenerans (Berlese) and T. saltus in Malawi. On other plants, the dominant phytoseiids were Euseius baetae, Amblyseius sundi Pritchard & Baker and Parphytoseius horrifer (Pritchard & Baker) in Mozambique, and I. degenerans,Euseius magucii (Meyer & Rodrigues) and Euseius orygmus (Ueckermann & Loots) in Malawi. Several of the most common plants associated with cassava were observed to harbor phytoseiid species that were also found on the latter. Those plants may be important as reservoirs of such predators when conditions are not appropriate for them to live on cassava. This seemed to be particularly true for 6 phytoseiids in Mozambique (A. sundi, E. magucii, P. horrifer, Typhlodromalus spinosus(Meyer & Rodrigues), Typhlodromips shi (Pritchar & Baker) and Neoseiulus teke (Pritchard & Baker)), and 6 phytoseiids in Malawi (E. orygmus, Phytoseius amba Pritchard & Baker, T. shi, Typhlodromus (Anthoseius) kikuyuensis Swirski & Ragusa, Typhlodromus (Anthoseius) malawiensis Annou, Moraes & Hanna and N. teke), that were found on cassava at the end of the rainy season, but only on other plants in the dry season. M. tanajoa was the dominant mite species on cassava in both countries in addition to the phytoseiids; few other species were found on that plant in either country. A larger diversity of mites in addition to phytoseiids was found on other plants, but always at low numbers. Phytoseiids diversity and abundance varied between savannah and forest zones. These variations are likely due differences in biotic and abiotic factors between the two zones.